Early dose optimization of golimumab induces late response and long-term clinical benefit in moderately to severely active ulcerative colitis. (3rd July 2019) - Taxonera, Carlos; Iborra, Marisa; Bosca-Watts, Marta Maia; Rubio, Saioa; Nantes, Óscar; Higuera, Rebeca; Bertoletti, Federico; Martínez-Montiel, Pilar; Sierra-Ausin, Mónica; Manceñido, Noemí; Lázaro Pérez-Calle, José; Algaba, Alicia; et al.
Abstract: Aim: To evaluate outcomes of early dose optimization of golimumab in ulcerative colitis (UC) patients with inadequate response to golimumab induction treatment. Methods: This observational, multicenter, cohort study included patients with moderate-to-severe active UC and with inadequate response to subcutaneous golimumab induction doses, in whom weight-based golimumab maintenance dose (European labeling) of 50 mg every 4 weeks (q4wk) was optimized before week 14 to 100 mg q4wk. At week 14, we assessed clinical response and remission using the partial Mayo score. In the long term we evaluate the cumulative probabilities of golimumab failure-free survival and colectomy-free survival. Results: A total of 209 patients who received golimumab induction doses were eligible. Of these, 151 patients (72.2%) weighing less than 80 kg were assigned to a golimumab maintenance dose of 50 mg q4wk. Twenty-four patients (15.9% [12.5% overall]), in whom scheduled doses of 50 mg q4wk were optimized to 100 mg q4wk before week 14, compose the study population. At week 14, 16 patients (66.7%, 95% CI 45.7–87.6) had clinical response, of these 12 were corticosteroid free. Four patients (16.7%) achieved corticosteroid-free remission. After a median follow-up of 12 months (IQR 10–22), 13 patients (54.2%) maintained clinical benefit. Thirteen of 16 patients (81.2%) with clinical response at week 14 maintained clinical benefit at last follow-up. All patients avoided colectomy. In none of the patients was golimumab dose de-escalated. There were no adverse events leading to golimumab withdrawal. Conclusion: Early optimization of golimumab dose induces clinical response at week 14 in two thirds of UC patients and leads to long-term clinical benefit in over half of patients.